Multifunctional "Click" Prolinamides: A New Platform for Asymmetric Aldol Reactions in the Presence of Water with Catalyst Recycling. Issue 2 (25th January 2013) - Paladhi, Sushovan; Das, Joydeb; Mishra, Pratyush Kumar; Dash, Jyotirmayee
Abstract "Click" chemistry is combined with organocatalysis to fabricate a multifunctional C3‐symmetrical dendritic prolinamide with a hydrophobic aromatic core and hydrophilic triazolinium arms that exhibit high efficiency in catalyzing the asymmetric aldol reaction with cyclic ketones. The catalyst is water‐compatible and remains active for five consecutive catalytic runs with a low catalyst loading (2 mol%), yielding the aldol products in high yields, diastereo‐ and enantioselectivities.